Dynamics of the time perspective of students youth of the south-eastern areas of Ukraine in the conditions of socioeconomic changes - Senyk, O.; Abramov, V.; Hrechkosiy, M.; Bedan, V.; Bunas, A.; Lutsenko, O. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
This paper focuses on the time perspective dynamics of the Ukrainian 17–24-year-olds which reside in the south-eastern regions of Ukraine, such as Kharkov, Dnepropetrovsk and Odessa regions, during the period 2012–2015. The study included areas bordering the zone of military conflict, or those that are an area of great national importance and therefore are a strategic area in military operations, which can begin there. All subjects filled out a personal data questionnaire (age, gender, place of residence) and the Zimbardo Time Perspective Inventory (ZTPI) in the Ukrainian-language adaptation by A. Senik or the Russian-language adaptation by A. Syrtsova. Thus, the research has covered three periods which differ in social, political and economical stability: before Maidan, during Maidan and the one started with onset of armed conflict in the Eastern regions of the country. The temporal perspective of young people, measured during these periods, may also differ because of changes in the social and material parameters of life. The results have shown that during the aforementioned period future time orientation decreases, whilst the numbers of present fatalistic and past negative time orientations as well as a negative interpretation of past events increase with onset of armed conflict in the Eastern regions of the country. The significance of time orientations does not differ in the period before the Maidan and in the Maidan period, and grow only in the period from the outbreak of the military conflict – simultaneously with significant changes in the social and material parameters of the population life living near the military conflict zone. The results obtained – a decrease in the setting of long-term goals, an increase in fatalism (helplessness) and a negative assessment of the past – may be the result of the young people traumatic experience, through the prism of which past, present and future events of one's own life are evaluated.
Keywords: time perspective; time orientation; Maidan; Eastern Ukraine